DFT, molecular docking, antimicrobial activity, dye degradation, and oxygen evolution reaction of functionalized chitosan integrated eudragit-stannous selenide nanostructures - Fatima, Areej (2025)
A chemical coprecipitation route was employed to synthesize stannous selenide (SnSe) nanostructures (NSs) integrated with a fixed amount of eudragit L100 (Eud) and different concentrations of chitosan (CS). This study aimed to examine rhodamine B (RhB) reduction catalytically, oxygen evolution reaction (OER), and antimicrobial properties of CS/Eud-SnSe. Several characterization techniques were employed for morphological, structural, and optical analysis of prepared NSs. The optimized sample (4 % CS/Eud-SnSe) revealed considerable RhB reduction efficacy in an acidic medium as well as effective antibacterial activity against S. aureus. Molecular docking substantiated the suppressive role of CS/Eud-SnSe against DNA gyraseS. aureus, elaborating on their bactericidal effect. Moreover, 4 % CS/Eud-SnSe proved an efficient material for OER activity, depicting the lowest overpotential, Tafel slope, and Rct value.